A Inserção da Competência Informacional nos currículos dos cursos de Biblioteconomia no Brasil e de Informação e Documentação na Espanha - Mata, Marta Leandro da [UNESP] (2014)
Nowadays, scientific researches are focused on the social responsibility of the librarian in his/her action towards the information society. It is understood that the librarian's professional formation should include content that focus on his/her social role, particularly on issues relating to information literacy, as the librarian is appointed as responsible for promoting, developing and implementing such programs in educational institutions. The present research aimed to analyze how the information literacy and pedagogical training content have been covered in Library Science courses in Brazil and for Information and Documentation on Spain, being characterizing itself as an exploratory, documentary and comparative research, in which analysis of curriculum, educational plans and interviews with teachers who teach on the subject discipline are made. Thus, the analysis of the results has been performed both qualitatively and quantitatively. As a result, in Brazil, it was found that there are 10 disciplines of information literacy, seven that are mandatory and three are optional; the nomenclature used is informational competence. In Spain, four are optional and only one in basic training. There is a standardization on the use of the term information literacy or informational literacy. The content of most disciplines that approach the theme includes the concept, programs, places of learning and the educational role of the librarian, considering that few courses in Library Science have didactic disciplines or education that enable students to understand the educational system, its organizational form, its learning theories. In the Spanish context, not disciplines of education are offered. However, students have the option to get their higher education as an elective discipline in other courses. It is considered that some courses of Information Science and Information and Documentation have returned...